Decoding the Dynamics of Leverage and Accounting Conservatism: Firm Size as a Key Moderator - Yulianti, Vista; Widayanti, Erlina; Purba, Jamian (Pusat P2M Politeknik Negeri Batam, 2026)
This study investigates the effect of leverage on accounting conservatism and examines the moderating role of firm size in this relationship. The research is motivated by the need to understand how financial structure influences conservative reporting practices within the framework of agency theory, particularly in manufacturing firms. A quantitative approach is employed using panel data regression analysis based on 85 firm-year observations derived from manufacturing companies listed on the stock exchange over the 2020–2022 period. The sample is selected using purposive sampling to ensure the availability of complete and relevant financial data. Multiple linear regression models are applied, incorporating interaction terms to test the moderating effect of firm size. The findings indicate that leverage has a significant positive effect on accounting conservatism, suggesting that firms with higher debt levels tend to adopt more prudent financial reporting practices to reduce potential conflicts between managers and creditors. Furthermore, firm size is found to significantly moderate this relationship, where larger firms demonstrate a stronger influence of leverage on conservatism due to greater external monitoring, regulatory pressure, and reputational concerns. In contrast, smaller firms exhibit a relatively weaker relationship, which may be attributed to limited resources and lower levels of stakeholder scrutiny. This study concludes that both leverage and firm size play important roles in shaping accounting conservatism. The results emphasize the importance of considering firm-specific characteristics when evaluating financial reporting behavior. The study contributes to the development of accounting literature by providing empirical evidence on the interaction between financial structure and organizational scale in influencing conservatism. The findings offer practical implications for managers, investors, creditors, and regulators in promoting transparency, accountability, and effective financial decision-making.